PENGARUH JUMLAH PENDUDUK, JUMLAH INDUSTRI, DAN PDRB TERHADAP LUAS LAHAN SAWAH DI DAERAH ISTIMEWA YOGYAKARTA TAHUN 1984-2013 - Yus Kasyfurrahman (EKPI 16 UMY 077, 2016)
*77 GDP against vast rice fields in Daerah Istimewa Yogyakarta. This is done because of the vast rice fields each year over the function of agricultural land to non-agricurtural, while the rice fields is very important to produce food especially in rice. Over the function of the rice fields caused by the increase in the number of people requires the land to colonize. The industry also became the cause of the diminution of wide fields because the industry needs land for establishing the building. Over the function of the rice fields in Daerah Istimewa Yogyakarta happens almost every year due to the growth of the population, industries and GDP significantly. This research was conducted using classic linear regression model (OLS). There is a classical regression assumption are presented in this study, namely non Autocorrelation, Homoscedasticity, and Multicollinearity. Based on the analysis that has been done, it is known outcome, namely population, industries, and GDP significantly and negatively related to the wetland area in the of Daerah Istimewa Yogyakarta Keywords: Total Population, Total Industry, and GDP.